Come home already! - John, Jory; Davies, Benji (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2018)
When Duck goes to visit his neighbor Bear, he finds a sign that says he's gone fishing for a whole week.
Keywords: Ducks -- Fiction; Bears -- Fiction; Friendship -- Fiction; Ducks -- Fiction; Bears -- Fiction; Friendship -- Fiction